1999
DOI: 10.1023/a:1006118827167
|View full text |Cite
|
Sign up to set email alerts
|

Sentinel lymphadenectomy in breast cancer: identification of sentinel lymph node and detection of metastases

Abstract: Sentinel lymphadenectomy is a useful way of assessing axillary status and obviating axillary dissection in patients with node-negative breast cancer. However, controversies remain concerning the optimal method to identify the sentinel lymph node (SLN) and detect micrometastases in this lymph node. We reviewed the literature concerning sentinel lymphadenectomy in breast cancer and reached the following conclusions: (a) A combination of preoperative lymphoscintigraphy with intraoperative dye-guided and gamma pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
3

Year Published

1999
1999
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 32 publications
1
6
0
3
Order By: Relevance
“…Others have found similar results clearly demontrating the usefulness of immunohistochemistry (7,10,12,13). Frozen section microscopy was not used in this study but several workers have investigated the feasibility and value of frozen section microscopy (4,(9)(10)(11)(12)(13)(14).…”
Section: Discussionsupporting
confidence: 53%
“…Others have found similar results clearly demontrating the usefulness of immunohistochemistry (7,10,12,13). Frozen section microscopy was not used in this study but several workers have investigated the feasibility and value of frozen section microscopy (4,(9)(10)(11)(12)(13)(14).…”
Section: Discussionsupporting
confidence: 53%
“…American investigators have used 99m Tc-radiolabelled sulphur colloid 16,30,31 because 99m Tc-labelled colloidal albumin is not commercially available in the USA. In the initial studies the ideal size of the radioisotope tracer was thought to be between 10 and 200 nm 16,26,32 and so 99m Tcradiolabelled ®ltered sulphur colloid (particle size less than 200 nm) was used. However, some investigators 30,31 have suggested that un®ltered 99m Tc-labelled sulphur colloid is preferable.…”
Section: Optimal Particle Size Of Radioisotope Tracersmentioning
confidence: 99%
“…Since Giuliano et al (1994) used 1.0% isosulfan blue (IB) for breast SLNB, doctors from different countries have tried various dyes with a view to achieve best results of SLNB. Till now, several vital dyes have been developed, like IB, patent blue (PB) (Koller et al, 1998;Noguchi et al, 1999) and methylene blue (MB). IB and PB, for a weak combination of protein will be quickly absorbed into lymph vessels after subcutaneous injection, and rarely spread to surrounding tissues.…”
Section: Introductionmentioning
confidence: 99%